IMPLEMENTATION OF INTERNAL AUDIT TOWARDS THE IMPLEMENTATION OF THE MINISTER OF FINANCE REGULATION NUMBER 112/PMK.03/2022 IN YOGYAKARTA CITY - Abdul Rahman, Raden Alem Janitra; Astuti, Susi (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
Economic and financial dynamics continue to develop in the application of regulations.Financial management is essential for entities to achieve good governance and enhance optimal accountability. Minister of Finance Regulation No. 112/PMK.03/2022 serves as the regulatory framework that provides direction regarding entity financial governance. The provisions of this Ministerial Regulation require entities to implement transparent and accountable financial practices. This obligation aligns with the spirit of improving financial governance, where entities are required to be financially responsible and ensure the integrity of financial information. Internal audit is at the forefront of ensuring that entities' financial practices comply with applicable regulations. Therefore, a thorough understanding of internal audit procedures in this context is essential. Audit theory refers to a set of principles and concepts that guide audit practice. Audit practice is designed to ensure that the financial information presented by an entity is reliable, transparent, and meets standards. The primary objective of an audit is to provide stakeholders with assurance that an entity's financial statements are accurate, reliable, and comply with accounting standards. This study aims to identify and analyze the contribution of internal audit to supporting entities in implementing financial regulations, specifically Minister of Finance Regulation No. 112/PMK.03/2022. Furthermore, this study aims to evaluate the effectiveness of internal audit in achieving optimal compliance with financial regulations. This study employed a mixed quantitative approach, encompassing document analysis and interviews. Internal audit findings play a crucial role in assessing the effectiveness and efficiency of regulatory implementation. Internal audit is effective in its responsibility to ensure business entities comply with applicable tax regulations.